Primed Authenticity: How Priming Impacts Authenticity Perception of Social Media Influencers. Issue 4 (8th August 2019) - Luoma-aho, Vilma; Pirttimäki, Tuisku; Maity, Devdeep; Munnukka, Juha; Reinikainen, Hanna
ABSTRACT: Though organizations increasingly collaborate with social media influencers, such as bloggers and videobloggers, little is known as to how the contextual cues related to sponsored content affect the authenticity perception of the social media influencers among audience members. This study explores how positive and negative priming of sponsored content shapes the authenticity perception of the vlogger among its audience members. Four different manipulation conditions were constructed to study a U.S. based travel vlog on Qualtrics, with data collected via Amazon's Mechanical Turk. A theory-guided content analysis of 211 open viewer responses was conducted to compare perceptions of authenticity between the manipulation groups. The results verified the significance of priming: the same sponsored content can result in opposite reactions among the audience members depending on the positive/negative valence of the introductory text attached, highlighting the central importance of strategic communication related to the perception of sponsored content. The results also point out the importance of audience member engagement for experienced authenticity: The manipulation of audience participation with the vlog had a stronger effect on the perception of authenticity of the vlogger than the positive/negative valence of the introductory text.